Toxicological studies on the aqueous leaf extract of Pavetta crassipes (K. Schum) in rodents - Moses W. Bariweni; Oboma I. Yibala; Raymond I. Ozolua (GarVal Editorial Ltda., 2018)
Context: Pavetta crassipes (K. Schum) is used in ethnomedicine for the management of various ailments and food without scientific report of its toxicity profile. Aims: To evaluate the toxicological effects of Pavetta crassipes leaves in rodents. Methods: The leaves of Pavetta crassipes were collected from the suburbs of Abuja, Nigeria, dried and powdered using an electric mill. Hot aqueous extraction was done using 250 g of the powdered leaf in 1000 mL distilled water. Lethal dose 50 (LD50) determination was done in mice (intraperitoneally) and rats (orally), twenty-eight-day toxicity testing in rats at doses of 400, 800 and 1600 mg/kg was also done using the aqueous extract. Biochemical, hematological and histological effects were evaluated using standard procedures. Results: The aqueous leaf extract of Pavetta crassipes (AE) appears safe as the LD50 for intraperitoneal route in mice and oral route in rats was greater than 5000 mg/kg. The results of the 28-day repeated exposure test produced no mortality or adverse effects on the body weights and organ/body weight ratio of rats. Histological changes occurred in the kidneys at 800 and 1600 mg/kg. There was a significant (p<0.01) reduction in AST, ALT, ALP and urea. Lymphocyte (%) and platelet count increased (p<0.01) but neutrophil (%) reduced (p<0.01). Conclusions: The LD50 of AE was greater than 5000 mg/kg but prolonged use at high doses may produce some adverse effects.